2000
DOI: 10.1093/milmed/165.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Human and Behavioral Factors Contributing to Spine-Based Neurological Cockpit Injuries in Pilots of High-Performance Aircraft: Recommendations for Management and Prevention

Abstract: In high-performance aircraft, the need for total environmental awareness coupled with high-g loading (often with abrupt onset) creates a predilection for cervical spine injury while the pilot is performing routine movements within the cockpit. In this study, the prevalence and severity of cervical spine injury are assessed via a modified cross-sectional survey of pilots of multiple aircraft types (T-38 and F-14, F-16, and F/A-18 fighters). Ninety-five surveys were administered, with 58 full responses. Fifty pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…We found two other prevalence studies including F-16 pilots: a study from 1988 found 58% of 200 F-16 pilots had experienced acute neck injury during the preceding 3 mo, with 13% of the injuries described as ' major ' with distal upper extremity symptoms ( 12 ), and a study from 2000 found 23 of 24 F-16 pilots had in-fl ight or postfl ight neck pain, the pain having a trend of being of longer duration and with right side lateralization when compared to pilots of the F-18, which has center stick control ( 6 ). Most injuries were described as muscle strain and stiffness and facet joint syndromes, but more serious injuries such as disc protrusions and bulges ( 4,10,11 ) and ligament injury and fractures ( 1,11 ) are described in the literature, as well as degeneration following long-term exposure to high 1 G z forces ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found two other prevalence studies including F-16 pilots: a study from 1988 found 58% of 200 F-16 pilots had experienced acute neck injury during the preceding 3 mo, with 13% of the injuries described as ' major ' with distal upper extremity symptoms ( 12 ), and a study from 2000 found 23 of 24 F-16 pilots had in-fl ight or postfl ight neck pain, the pain having a trend of being of longer duration and with right side lateralization when compared to pilots of the F-18, which has center stick control ( 6 ). Most injuries were described as muscle strain and stiffness and facet joint syndromes, but more serious injuries such as disc protrusions and bulges ( 4,10,11 ) and ligament injury and fractures ( 1,11 ) are described in the literature, as well as degeneration following long-term exposure to high 1 G z forces ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have drawn attention to the problem that pilots, in general, are reluctant to voluntarily provide accurate personal, medical-type information or complete detailed questionnaires ( 6 ). In this study, we endeavored to overcome this problem by tracking the completion of the questionnaires, well aware that this might be regarded as a kind of pressure and could result in perfunctory responses on some surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Performing high-G manoeuvres [41], pilot ejection [42], and helicopter vibration [43] present risk factors for injury to the neck. Potentially, the resulting high-compressive forces on the spine could result in end plate fractures, then leading to adjacent IVD degeneration [44].…”
Section: Cumulative Injury To the Ivd Prior To Spaceflightmentioning
confidence: 99%
“…Newman concluded that prefl ight stretching might not be protective in terms of G-induced neck injury ( 25 ). In the survey of Jones et al, prefl ight stretching did not appear to prevent fl ight-related pain; however, a more defi ned prefl ight stretching routine was recommended as a part of a potentially effective prevention strategy ( 20 ). One survey of 268 pilots showed that prefl ight range-of-motion stretching had a benefi cial effect ( 1 ).…”
Section: Functional Assessment In F-16 Pilots -De Loose Et Almentioning
confidence: 99%